Ultrafast emission decay with high emission efficiency of quantum dots in plasmonic–dielectric metasubstrates. (13th June 2017) - Wing, Waylin J; Sadeghi, Seyed M; Gutha, Rithvik R
Abstract: We report on the ultrafast decay of quantum dots that reaches nearly 430 ps without reduction in the emission intensity when near a metasubstrate of simple geometry. By implementing a layered structure of amorphous silicon sandwiched between two gold layers, the balance between plasmonic near field enhancement and energy transfer of the quantum dots has been shifted. This is achieved by tailoring the amount of Förster resonance energy transfer (FRET) to the top Au layer and plasmonic near field enhancement by the bottom Au layer. We also study the impact of deposition of Al oxide on the top Au layer, forming a charge barrier junction that can suppress Auger recombination of quantum dots. The results show that such a barrier can increase emission efficiency of the metastructure without significant reduction in the decay rate. We study the impact of formation of small nanoislands to contiguous islands via variation of the thickness of the top Au layer, and discuss how such morphologies determine the amount of FRET, screening of plasmonic field from the bottom Au layer, and enhancement of emission due to their own plasmonic fields.